A sociologia fenomenológica de Alfred Schutz - Fábio Fonseca de Castro (Ciências Sociais Unisinos)
This paper develops a bio-bibliographical review of the thought of Alfred Schutz and his project to set up a phenomenological sociology. Schutz's work operates at the confluence of Weber's comprehensive sociology with Husserl's phenomenology and can be understood from the perspective of an anti-essentialist theory whose main assumption is the rejection of a full rationality of the real. His proposal is to reestablish, phenomenologically, comprehensive sociology. However, in order to do it, it was necessary to develop a critique of Husserl¿s transcendental egology and put the theme of subjectivity in a sociological perspective, establishing the matrix of the idea of intersubjectivity -- something that goes beyond the mere constellation of individual subjectivities, inherent in Husserl's thought. Schutz's thought presents a solution to the problem of intersubjectivity in sociology by building the core framework of a phenomenological sociology.